PERANGKAP NYAMUK RAMAH LINGKUNGAN YANG MENGGUNAKAN BAHAN RAGI UNTUK PENGEMBANG BIAKAN KESTABILAN SUHU DENGAN HEAT DETECTOR YANG MENGGUNAKAN NTC ( NEGATIVE TEMPERATURE COEFFISIEN) - Enny, Enny (METANA, 2013)
Abstract Tool mosquito traps we encounter in our lives, be it in liquid or solid form, but there are some that contain chemicals. In the environment of our lives more and more developing mosquitoes due to less uncontrolled channels substandard and not arranged. And there are many people who use liquid or solid materials containing chemical substances, which can interfere with human comfort In this study makes tools that are environmentally friendly mosquito trap, this tool can be applied in the community, since it is also quite easy, does not require hazardous materials, comparatively simple and fast. With the creation of yeast and sugar solution will cause the fermentation process, where the results of this fermentation process will produce CO2 or carbon dioxide is a chemical compound that is the most interesting mosquitoes come. To control the temperature as well as the results of CO2 gas can develop rapidly so we set it up or put up with a tool such as a series heat detector that uses NTC (Negative Temperature Coeffisien) which can control the temperature ofÂ  25oC-30oC. Thus, the more carbon dioxide, the more mosquitoes were trapped. The results showed that use of the material I :( yeast = 1 gram = 50 grams of brown sugar, water = 250 ml) and material 2 (= 1 g Yeast, Brown sugar: 100gr, water = 250 ml) results are better materials 2 because these materials tend to be attractive / approachable mosquitoes, because the adhesions combined sugar yeast grow better and produce different yeast aroma of material 1 Keywords: mosquito trap, environmentally friendly